2016
DOI: 10.3389/fpls.2016.01077
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Genotype–Phenotype Associations in a Collection of Oat Landraces and Historic Cultivars

Abstract: Population structure and genetic architecture of phenotypic traits in oat (Avena sativa L.) remain relatively under-researched compared to other small grain species. This study explores the historic context of current elite germplasm, including phenotypic and genetic characterization, with a particular focus on identifying under-utilized areas. A diverse panel of cultivated oat accessions was assembled from the USDA National Small Grains Collection to represent a gene pool relatively unaffected by twentieth ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 63 publications
5
43
0
Order By: Relevance
“…In the tested accessions we did not found any links between genetic and morphological variation. A similar result was obtained in the study of Winkler et al [46]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the tested accessions we did not found any links between genetic and morphological variation. A similar result was obtained in the study of Winkler et al [46]. …”
Section: Discussionsupporting
confidence: 91%
“…Those studies based on bulk samples, so the internal diversity of oat accessions was not evaluated. In the most recent study performed on 1 000 oat accession from NSGC, DNA from only one plantlet per accession was analysed by iSelect 6K beaded chip array [46]. The authors identified as much as 324 lines as duplicates with one or many other lines.…”
Section: Discussionmentioning
confidence: 99%
“…QTL mapping for plant height is complicated by pleiotropic effects of genes controlling heading date (vernalization requirement and photoperiod sensitivity), as they affect duration of vegetative stage and therefore height of plant. In fact, many studies reported co-localization of QTLs for height with those for heading date or vernalization (Holland et al 1997;De Koeyer et al 2004;Wooten et al 2009;Winkler et al 2016). We also have found that the associations with plant height in Mrg01 and Mrg13 co-mapped with QTLs for heading date previously identified in this collection (Tumino et al 2016) and an association with plant height in Mrg11 co-mapped with a QTL for frost tolerance (Tumino et al 2016).…”
Section: Lodging Tolerance and Plant Heightmentioning
confidence: 52%
“…The recent development of new genomic tools, notably the 6K Infinium SNP array (Tinker et al 2014) and the dense hexaploid oat consensus map (12,000 markers) based on 12 bi-parental populations (Chaffin et al 2016;Yan et al 2016), have made it possible to map oat traits at a high resolution (Esvelt Klos et al 2016). Winkler et al (2016) used the array for a genome-wide association study (GWAS) in a diverse panel of oat accessions from the USDA National Small Grains Collection, assembled to represent a gene pool relatively unaffected by 20th century breeding activities, but failed to find significant associations for lodging tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation